Rapid Gardos Hereditary Xerocytosis Diagnosis in 8 Families Using Reticulocyte Indices - Picard, Véronique; Guitton, Corinne; Mansour-Hendili, Lamisse; Jondeau, Bernard; Bendélac, Laurence; Denguir, Maha; Demagny, Julien; Proulle, Valérie; Galactéros, Frédéric; Garçon, Loic (Frontiers in Physiology, 2021)
Gardos channelopathy (Gardos-DHS) is a constitutional haemolytic anaemia due to mutations in the KCNN4 gene. It is rarer than inherited type 1 stomatocytosis due to PIEZO1 mutations (Piezo1-DHS) and its diagnosis is particularly difficult given the absence of a specific clinical and biological phenotype. We report here that this diagnosis can be considerably accelerated by the analysis of red blood cell (RBC) indices performed on an ADVIA 2120 (Siemens ®) analyzer, which measures reticulocyte mean corpuscular volume (rMCV) and reticulocyte mean corpuscular hemoglobin concentration (rMCHC). We studied erythrocyte and reticulocyte indices in 16 patients (9 families) with Gardos channelopathy, compared to 91 patients with Piezo1-DHS. Among Gardos-DHS cases, 12 (7 families) presented the recurrent p.Arg352His mutation, 4 cases (2 families) presented a private KCNN4 mutation. By analyzing reticulocyte indices in Gardos-DHS, we observed that, in contrast with Piezo1-DHS, rMCV was smaller than that of the RBCs and rMCHC was higher. We then compared the differences ΔMCV (rMCV-MCV) and ΔMCHC (rMCHC-MCHC): ΔMCV was -0.9 ± 5 vs. 19.8 ± 3 fL (p<.001) and ΔCCMH: 18.7 ±13 vs. -50±8.7 g/L (p<.001) in Gardos and Piezo1-DHS respectively. Importantly, these observations proved to be correct for each individual subject, regardless of age, mutation or splenectomy. Consequently, these parameters enabled to suspect Gardos channelopathy on blood count results, allowing to rapidly target these patients for genetic analysis. This is of great interest in the context of haemolysis diagnosis since it allows the patient to be referred quickly without any additional cost for a genetic study.